Faktor Internal dan Eksternal Yang Mempengaruhi Pembiayaan Murabahah Pada Perbankan Syariah di Indonesia - Azmi, Fika (STIE Surakarta, 2015)
his research aims to examine internal and external factors that influence Murabaha Financing on Islamic banking In Indonesia. This research used five independent variables, that is Deposit Third Party Fund, Non Performing Financing, Murabaha Margin, Inflation and Bank Indonesia Certificates Sharia (SBIS). The population in this research are all Islamic banks, Islamic Business Unit (UUS), and Sharia Rural Banks (BPRS) in Indonesia. The sample consisted of three banks that are determined by purposive sampling technique. The criteria used that foreign Islamic bank that issued quarterly financial statements in the year 2010-2014. The hypothesis was tested using multiple regression analysis. The results of this research shows that Deposit Third Party Fund and Murabaha Margin have asignificant positive effect on Murabaha Financing. While the Non Performing Financing, Inflation and Bank Indonesia Certificates Sharia have no significant effect on Murabaha Financing